Medication Incidents Associated with Outpatient Computerized Prescribing Systems - Khan, Kayamkani Abedulla (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: A medication incident is any avertable event that may lead or cause to improper medication use or patient harm while the medication is in the control of the health-care professional, consumer, or patient. Professional practice, procedure, drug products, and systems may be related to medicated incidents. Objective: The main purpose of this study is to investigate these incidents such as types of prescribing errors, evaluate the occurrence of drug-drug interactions, and assess the rationality of e-prescription orders of outpatient. Materials and Methods: A cross-sectional study conducted between September 2019 and December 2019, to report the causes, frequency, and types of errors associated with outpatient computer-generated prescriptions, and to develop a framework to categorize these errors to determine which strategies have immense potential for preventing them. Three hundred thirty-nine patient’s prescriptions were included in the study over a period of 12 weeks and the data were collected from the outpatient pharmacy of different hospitals. Results and Discussion: It is observed that as an average, six drugs per prescription were prescribed. We observed 29 prescriptions are containing incomplete patient information that is 8.6% of prescriptions. We observed the majority of prescriptions were contain more than five drugs that are found in 159 prescriptions; around 47% of prescriptions are having more than five drugs. The current investigation focuses on the crucial character of the pharmacist in the prevention of medication errors or committed by physicians while ordering the e-prescriptions.